ACQUISITION OF EARLY CHILDHOOD PHONOLOGY : A CASE STUDY OF A 24 MONTHS TODDLER IN PALEMBANG - Aprilia, Fitria (English Community Journal, 2022)
This research aimed to describe the language acquisition of a toddler at the age of 24 months, seen from the phonological aspects, such as consonants, vowels, and diphthongs. This research was conducted in Palembang, on November – December 2021. The method used in this research was qualitative method through case study approach. The data were obtained from a toddler whose initial name was “MSM” as the respondent. The techniques for collecting the data were through observation and recording. The results of the analysis showed that the respondent was able to pronounce various phonemes existed in Bahasa Indonesia and Bahasa Palembang (Indonesian and Palembang Language). These phonemes consisted of 14 consonants which were /p/, /b/, /m/, /t/, /d/, /s/, /n/, /l/, /?/, /t?/, /j/, /g/, /k/, and /?/. The respondent also has been able to produce the vowels phonemes such as /a/, /i/, /u/, /e/, /?/ and /?/ and some kinds of diphthongs which were /a?/, /e?/, /a?/, and /??/.